Friction in orthodontics - Jaramillo-Vallejo, Pedro María; Salcedo-Ospina, Olga Bibiana (Revista Facultad de Odontología Universidad de Antioquia, 2023)
Friction is a fundamental aspect of orthodontic movement. Researchers and clinicians must be acquainted with its biomechanical and physical principles, as well as the potential alterations that may occur with the use of diverse materials. This literature review presents an approach of the physical principles at work in frictional mechanics, an analysis of the friction, at macro and microscopic level, of different orthodontic materials; describes the influence of friction on tooth movement and presents an update on friction research and its relationship to various materials.